Development of automated electrical heat grid for pavement snowmelt. (May 2019) - Daniels, Joseph W.; Heymsfield, Ernie; Saunders, Robert F.; Kuss, Mark L.
Abstract: Snow and ice on airfield pavement threatens aircraft ground operation safety. Plowing and chemical treatment are used for snow removal, but yield long-term detrimental impacts to the airfield infrastructure and environment. In this paper, a "near-surface embedded electrical heating grid prototype" is investigated through laboratory and field testing for concrete pavement heating, providing an airfield pavement anti-icing alternative. The prototype grid, installed on small-scale concrete test mats, was studied in a laboratory controlled below-freezing temperature environment. Testing evaluated pavement surface heating performance under two energy supply methods: (1) an alternating heating sequence and (2) an automated thermostat heating sequence, assessing their ability to (1) raise the pavement surface temperature to an anti-icing temperature threshold, 2 °C, and (2) sustain an anti-icing surface temperature. The alternating heating sequence required a low power input, but an increased heating time. Under the automated thermostat heating sequence, with a 152.4 mm parallel heat wire spacing and 667 W/m 2 power input, surface temperature rose from an initial −12 °C to 2 °C in 4 h, then maintained in the anti-icing range, 2 °C to 5 °C. Laboratory, preliminary study results directed the construction, instrumentation, and operation of a large-scale prototype slab for field testing. The prototype was built in Fayetteville, AR and subjected to ambient outdoor climate conditions. The full-scale testing used a photovoltaic energy system as the power source. Field testing assessed heating/anti-icing performance and energy consumption. During tests in below freezing air temperatures and snow events, the photovoltaic energy system supplied enough energy to maintain the large-scale prototype slab surface above 0 °C.